Effect of Canine Hyperadrenocorticism on Coagulation Parameters. (28th December 2012) - Rose, L.; Dunn, M.E.; Bédard, C.
<x xml:space="preserve">Abstract</x> Background Hyperadrenocorticism (HAC) has been associated with thrombotic disease in dogs. Hypothesis The purpose of this study was to use thromboelastography (TEG) and measurement of thrombin generation (TG) to characterize the hypercoagulable state in dogs with HAC. We hypothesized that dogs with HAC would have a hypercoagulable profile on TEG tracings and an increase in thrombin generation as measured by endogenous thrombin potential (ETP). Animals Sixteen dogs with HAC. Dogs were compared with a population of normal dogs used to obtain reference intervals. Methods TEG tracings on citrated whole blood were obtained from 15 dogs, and TG measurements on frozen‐thawed platelet‐poor plasma (PPP) were obtained from 15 dogs. Results For the TEG analysis, when results of individual dogs were compared with the reference interval, 12/15 dogs had at least 1 parameter associated with hypercoagulability. When the population of HAC dogs was compared with a population of healthy dogs, HAC dogs had decreases in R and K and increases in α and MA values. The ETP was increased when the HAC group was compared with a population of normal dogs. However, only 3/15 dogs had an ETP above reference interval, and 1/15 had a decreased lag time. Conclusion and Clinical Importance Of 16 dogs with HAC, 12/15 had evidence of hypercoagulability when evaluated by TEG, 4/15 when evaluated by TG, and 2 dogs had increases in ETP and MA.